Mitigation of IUI in Automotive Radar Based on OFDM Scheme - F. Yousefian; R. Mohseni (IEEE Access, 2025)
With rapid development of self-driving technology, automotive radars face more challenges, especially in dealing with interference in rush hour traffic. Interference from nearby radar-equipped vehicles, named inter-user-interference (IUI), can significantly degrade radar performance and compromise the accuracy and safety of vehicle operations. Orthogonal Frequency Division Multiplexing (OFDM) radar, with its capability of utilizing orthogonal coding, presents a suitable solution to effectively mitigate inter-user interference. This paper discusses the necessity of interference mitigation in automotive radar systems and examines how orthogonal coding, particularly through a proposed specific type of generalized chirp-like (ST-GCL) sequences, can reduce the interference and improve the system performance in key metrics such as velocity and range. For more analysis, a comparison between proposed OFDM and Frequency Modulated Continuous Wave (FMCW) radar, is provided that emphasizes the advantages of OFDM in heavy-interference scenarios.